Dynamic modeling and simulation of 10hp induction motor driving a variable load - Stephen Ejiofor, Oti; Candidus, Eya; Stephen, Agada; Ogbuefi, Uche; Peter, Ugwuja (International Journal of Engineering and Technology, 2020)
This work presents ideally the behavioral characteristics of induction motor (IM) when subjected to different loading conditions. The task is achieved via mathematical modeling of the process using the Simulink tool of the Matlab. Dynamic model is generally used to study the steady state and transient behavior of induction motor. Here, Clarke and Parkâ€™s transformation of stator and rotor parameters on the synchronously rotating reference frame is applied to the developed mathematical model of the induction motor. First, the differential equations of voltages, currents and flux linkages between the stationary stator and rotating rotor are developed, followed by the mechanical equation of torque and speed. Thereafter the mathematical model developed with the help of the software is generally used to study the variation in parameters value on the dynamic performance of the induction motor as variable load is driven. The obtained simulated results apart from the exhibited performances still suggests that the synchronously rotating reference frame theory is actually a shrewd process to validate the dynamic behavior of the induction motor. Â Â Â